Reliability and Validity of Athletes Disability Index Questionnaire. Issue 2 (March 2018) - Noormohammadpour, Pardis; Hosseini Khezri, Alireza; Farahbakhsh, Farzin; Mansournia, Mohammad Ali; Smuck, Matthew; Kordi, Ramin
Abstract : Objective: The purpose of this study was to evaluate validity and reliability of a new proposed questionnaire for assessment of functional disability in athletes with low back pain (LBP). Design: Validity and reliability study. Setting: Elite athletes participating in different fields of sports. Participants: Participants were 165 male and female athletes (between 12 and 50 years old) with LBP. Interventions: Athlete Disability Index (ADI) Questionnaire which is developed by the authors for assessing LBP-related disability in athletes, Oswestry Disability Index (ODI), and the Roland-Morris Disability Questionnaire (RDQ). Main Outcome Measures: Self-reported responses were collected regarding LBP-related disability through ADI, ODI, and RDQ. Results: The test–retest reliability was strong, and intraclass correlation value ranged between 0.74 and 0.94. The Cronbach alpha coefficient value of 0.91 ( P < 0.001) demonstrated excellent internal consistency of the questionnaire. The correlation coefficient between ADI and ODI was r = 0.918 ( P < 0.0001), between ADI and RDQ was r = 0.669 ( P < 0.0001), and between ADI and visual analog scale was r = 0.626 ( P < 0.001). According to ODI and RDQ, disability levels were mild in the large majority of subjects (91.5% and 86.0%, respectively). Alternatively, disability assessments by the ADI did not cluster at the mild level and ranged more broadly from mild to very high. Conclusion: The ADI is a reliable and valid instrument for assessing disability in athletes with LBP. Compared with the available LBP disability questionnaires used in the general population, ADI can more precisely stratify the disability levels of athletes due to LBP.